PENGARUH STORE ATMOSPHERE TERHADAP MINAT BELI KONSUMEN PADA KAFE U & ME TANJUNG - Nadi Fikri Rijali (Jurnal PubBis, 2023)
The purpose of this study is to determine the impact of store atmosphere on consumer purchasing interest at the U & Me Tanjung Cafe.Customers of U & Me Cafe make up the population of this study. The sample size in this study was 67 people, with a sampling technique of non-probability sampling and a sample size determined by convenience sampling. Data was gathered through a survey or questionnaire distributed to respondents. The Generalized Structured Component Analysis (GesCA) analysis tool is used in this study. The study's findings indicate that store atmosphere has a significant impact on purchase intent. The findings of this study suggest that a store environment that meets consumer expectations will entice customers to make purchases. Furthermore, a positive store atmosphere is one of the factors that determines the company's long-term viability. Keywords: Store atmosphere, Purchase Intention, U & Me Cafe